THE ROLE OF CITY IMAGE AND VISITORS'SATISFACTION ON VISITORS'REVISIT INTENTION: A STUDY IN AN ENCLAVE CITY - Mujihestia, Tita Imamelina; Troena, Eka Afnan; Hussein, Ananda Sabil (Universitas Brawijaya, Indonesia, 2018)
This study aims to determine the influence of city image on visitors'revisit intention at Malang, Indonesia. This study also examines the influence of visitors'satisfaction on the paths from perceived image to visitors'revisit intention. This study uses a quantitative explanatory approach. The primary data were obtained using a questionnaire addressed to 180 visitors'who ever visit Malang for a holiday reason only. Analysis of the data used is Partial Least Square (PLS) with PLS-Path Modelling (PLS-PM) method. The results of this study are: first, visitors'perceived image about city plays an important role in enhancing visitors'revisit intention. Second, visitors'satisfaction directly affects to visitors'satisfaction. Third, visitors'satisfaction partially mediated the relationship between city image and visitors'revisit intention.